Integrative Korean Medicine Treatment for Idiopathic Glossopharyngeal Neuralgia: A Case Report - So Jeong Kim; Hyeon Kyu Choi; Min Ju Kim; Hyun Ji Cha; Young Rok Lee; Hyun Jin Jang; Jeong Kyo Jeong; Ju Hyun Jeon; Young Il Kim (MEDrang Inc., 2022)
Glossopharyngeal neuralgia is a skin-sensitive condition/disease that causes severe pain in the facial area predominantly innervated by the glossopharyngeal nerve. A 51-year-old man diagnosed with glossopharyngeal neuralgia who was hospitalized with severe pain that limited his daily life activities. From November 18, 2021, to March 4, 2022, he received inpatient (10 days) and outpatient treatment (35 times) using acupuncture, pharmacopuncture, and herbal medicine. His symptoms were assessed using the Numerical Rating Scale, Neuropathic Pain Scale, and the Self-report Leeds Assessment of Neuropathic Symptom and Signs. The pain reduced after 4 days of initiating Korean medicine treatment and was completely resolved within 4 months of treatment (Numerical Rating Scale score 4 to 0; Neuropathic Pain Scale score 49 to 8; Self-report Leeds Assessment of Neuropathic Symptoms and Signs score 18 to 0). Korean medicine treatment could be an option for treating patients with neuropathy who rely on analgesics.